GPS as an independent measurement to estimate terrestrial water storage variations in Washington and Oregon. Issue 1 (12th January 2015) - Fu, Yuning; Argus, Donald F.; Landerer, Felix W.
Abstract The Global Positioning System (GPS) measures elastic ground loading deformation in response to hydrological mass variations on or near Earth's surface. We present a time series of change in terrestrial water storage as a function of position in Washington and Oregon estimated using GPS measurements of vertical displacement of Earth's surface. The distribution of water variation inferred from GPS is highly correlated with physiographic provinces: the seasonal water is mostly located in the mountain areas, such as the Cascade Range and Olympic Mountains, and is much smaller in the basin and valley areas of the Columbia Basin and Harney Basin. GPS is proven to be an independent measurement to distinguish between hydrological models. The drought period of 2008–2010 (maximum in 2010) and the recovery period of 2011–2012 in the Cascade Range are well recovered with GPS‐determined time‐variable monthly water mass series. The GPS‐inferred water storage variation in the Cascade Range is consistent with that derived from JPL's GRACE monthly mass grid solutions. The percentage of RMS reduction is 62% when we subtract GRACE water series from GPS‐derived results. GPS‐determined water storage variations can fill gaps in the current GRACE mission, also in the transition period from the current GRACE to the future GRACE Follow‐on missions. We demonstrate that the GPS‐inferred water storage variations can determine and verify local scaling factors for GRACE measurements; in the Cascade Range, the RMS reduction between GRACE series scaled by GPS and scaled by the hydrological model‐based GRACE Tellus gain factors is up to 90.5%.